Territoriality Characteristics in Housing of Kampung Bugis, Buleleng Regency, Bali - Ocean Dewata, Kadek; Ketut Agusintadewi, Ni; Anggraini Prajnawrdhi, Tri (Universitas Ibn Khaldun Bogor, 2023)
One of the less well-organized residential areas in Buleleng is the Kampung Bugis settlement. The development of the Bugis Village settlement as one of the densest settlements in Buleleng does not get good regulation and control so that the village environment tends to be slum, disorganized, uncomfortable and unhealthy. The existence of Bugis Village which is increasingly dense by residents also has an impact on the density of buildings in residential areas. Unfortunately, this condition is not balanced with the arrangement and sufficient land area. Due to the high environmental pressure, residents become spatially motivated by creating